Efektifitas Edukasi Gizi Melalui Media Booklet Tentang Pemberian Makanan Tambahan (PMT) Pada Balita Wasting - Nathasa Weisdania Sihite; Manuntun Rotua; Ayu Cintiya; Ridhotun Annisa; Omega Tri Grese (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Wasting is a nutritional problem that often occurs in Indonesia. Handling the problem of wasting can be done in many ways, one of which is to carry out nutrition education that is right on target. Community service activities aim to provide knowledge about the effectiveness of supplementary feeding (PMT) in dealing with wasting problems in the form of educational media, namely the pocketbook "Booklet". The method carried out is nutrition education in the form of counseling using printed media "Booklet" which can be used as a daily guide. Providing material in the form of lectures, discussions, and questions and answers related to the material. The results showing of the activities carried out, it was found that many of the participants enthusiastically received the material presented and appreciated the pocketbook that was given. Nutrition education in the form of educative media-based counseling which is important to do, in addition to the program targets getting nutritional knowledge, the targets will also receive guidelines that can be used as a reference for the administration of supplementary feeding (PMT) for wasting toddlers. This is certainly expected to help overcome and reduce waste incidents in the surrounding area